Heckscher-Ohlin explained by Walras - Yves Balasko (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
The Heckscher-Ohlin model with arbitrary number of goods, factors and countries (consumers) and no restrictions on factor trading is shown to be equivalent to an exchange model whose goods are the productive factors while consumer's indirect demands for factors are derived from their actual demands for consumption goods. This equivalence enables one to import properties like the path connectedness of the equilibrium manifold, the uniqueness of equilibrium for sufficiently small volumes of trade and discontinuities of equilibrium selection maps for large volumes of trade into the Heckscher-Ohlin model.This equivalence also provides the proper theoretical background to the important but so far purely empirical role played in international trade by the volume of net trades in factor contents.
Keywords: D51; F11; F14; 330; Heckscher-Ohlin; general equilibrium; international trade; factor content